Digital Sexual Practices, Consensual and Non‐Consensual Experiences and Wellbeing Consequences in the CSF ‐2023 French National Survey - Armelle Andro; Rim Bellamine; Aline Bohet (Perspectives on Sexual and Reproductive Health, 2026)
ABSTRACT Introduction Digital technologies have reshaped relationships and sexual practices, both in terms of sexual well‐being and through the emergence of cyberharassment. However, evidence remains limited, however, on how these practices vary by gender, generation, sexual orientation, and social position. This article aims to describe the frequency of online sexual experiences and their correlates in a large national sample. Methods The study draws on CSF‐2023, a cross‐sectional survey of sexuality in France. The sample comprises 15,906 individuals aged 18–59 who reported information on their online practices. We analyze the frequency of these experiences and their associations with gender, generation, sexual orientation, and educational level, using univariate and multivariate analyses. Results Men reported online sexual experiences more often than women (58% vs. 46%). Sending intimate images was reported by 21% of women and 25% of men, and receiving them by 28% and 33% respectively. These practices were more frequent among younger respondents and among people who had same‐sex partners, with older generations having taken them up later in life. A marked gender contrast emerged for negative experiences: while they affected 19% of women and 17% of men aged 18–59, the gap widened sharply among 18–29‐year‐olds (33% of women vs. 25% of men). Single women and people in poor health were more exposed; among men, risk was highest for those who had same‐sex partners and a low level of education. Conclusion Digital practices can be positive, but they can also lead to harmful exposure with deleterious effects, which particularly affect young women. There is a need to develop lifelong education about these new forms of intimate exchange, together with support measures for people confronted with these new forms of sexual violence.